2018
DOI: 10.1007/s12039-018-1418-3
|View full text |Cite
|
Sign up to set email alerts
|

Formic acid assisted hydrogenation of levulinic acid to $$\upgamma $$ γ -valerolactone over ordered mesoporous $$\hbox {Cu/Fe}_{2}\hbox {O}_{3}$$ Cu/Fe 2 O 3 catalyst prepared by hard template method

Abstract: Vapor phase hydrogenation of levulinic acid using formic acid as a hydrogen source has been conducted over ordered mesoporous Cu/Fe 2 O 3 catalysts prepared by hard template method using mesoporous silica, SBA-15. X-ray diffraction result reveals the absence of copper peaks because of either highly dispersed state, or formation of a solid solution with iron oxides. The N 2 sorption analysis and TEM results indicate the retainment of mesoporous nature in the samples. Among the catalysts tested, 10 (wt%) Cu/Fe 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 37 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…The highest activity corresponded to Mn 2 Co 0.1 O x of 83.4% LA conversion and 70% GVL selectivity achieved at 230 C. The improved activity was attributed to the structural distortion induced at MnCoO 3 and MnO x interface, which facilitated the adsorption of FA by H-H formation and p-p interaction with ketone group of LA simultaneously. Previous attempts for applying non-noble metals in hydrogenating LA into GVL using FA in vapour phase [96][97][98][99][100][101] and in aqueous phase [102][103][104][105][106][107][108] are published elsewhere. Amongst, deactivation was studied by Hussain Sk et al 101 who found that using pure MgO catalyst exhibited good activity at the start-up before it declines due to deactivation.…”
Section: Formic Acid: a Hydrogen Donor For Hydrogenation Of Levulinic...mentioning
confidence: 99%
“…The highest activity corresponded to Mn 2 Co 0.1 O x of 83.4% LA conversion and 70% GVL selectivity achieved at 230 C. The improved activity was attributed to the structural distortion induced at MnCoO 3 and MnO x interface, which facilitated the adsorption of FA by H-H formation and p-p interaction with ketone group of LA simultaneously. Previous attempts for applying non-noble metals in hydrogenating LA into GVL using FA in vapour phase [96][97][98][99][100][101] and in aqueous phase [102][103][104][105][106][107][108] are published elsewhere. Amongst, deactivation was studied by Hussain Sk et al 101 who found that using pure MgO catalyst exhibited good activity at the start-up before it declines due to deactivation.…”
Section: Formic Acid: a Hydrogen Donor For Hydrogenation Of Levulinic...mentioning
confidence: 99%
“…Most of the copper-based catalysts have been used to convert levulinic acid and its derivatives into GVL under vapor phase hydrogenation conditions, which are carried out at high temperature and long reaction time (entries 6 to 9). 14,36,37,61 One of the features of this study is the production of GVL under solvent-free conditions, which, in addition to being eco-friendly, makes it easier to separate and analyze the product. For this reason, this study can be compared with the report of Yuan etc.…”
Section: Catalyst Reusabilitymentioning
confidence: 99%
“…Recently, instead of using free hydrogen gas (i.e., traditional hydrogenation), the sources of hydrogen such as ammonia borane [36], dimethyl ammonia borane [37], liquid methanol [38], formic acid [39], and sodium borohydride [40][41][42] have been given preference. Of them, NaBH4 is quite stable, cheaper, eco-friendly, and water soluble that can be used under mild reaction conditions.…”
Section: 4'-bipyridinementioning
confidence: 99%